Notch2 Increases the Resistance to Venetoclax-Induced Apoptosis in Chronic Lymphocytic Leukemia B Cells by Inducing Mcl-1 - Fiorcari, Stefania; Maffei, Rossana; Atene, Claudio Giacinto; Mesini, Nicolò; Maccaferri, Monica; Leonardi, Giovanna; Martinelli, Silvia; Paolini, Ambra; Nasillo, Vincenzo; Debbia, Giulia; Potenza, Leonardo; Luppi, Mario; et al. (Frontiers in Oncology, 2022)
Chronic lymphocytic leukemia (CLL) has experienced a clinical revolution—thanks to the discovery of crucial pathogenic mechanisms. CLL is still an incurable disease due to intrinsic or acquired resistance of the leukemic clone. Venetoclax is a Bcl-2 inhibitor with a marked activity in CLL, but emerging patterns of resistance are being described. We hypothesize that intrinsic features of CLL cells may contribute to drive mechanisms of resistance to venetoclax. We analyzed the expression of Interferon Regulatory Factor 4 (IRF4), Notch2, and Mcl-1 in a cohort of CLL patients. We evaluated CLL cell viability after genetic and pharmaceutical modulation of Notch2 expression in patients harboring trisomy 12. We tested venetoclax in trisomy 12 CLL cells either silenced or not for Notch2 expression or in combination with an inhibitor of Mcl-1, AMG-176. Trisomy 12 CLL cells were characterized by low expression of IRF4 associated with high levels of Notch2 and Mcl-1. Notch2 and Mcl-1 expression determined protection of CLL cells from spontaneous and drug-induced apoptosis. Considering the involvement of Mcl-1 in venetoclax resistance, our data demonstrated a contribution of high levels of Notch2 and Mcl-1 in a reduced response to venetoclax in CLL cells carrying trisomy 12. Furthermore, reduction of Mcl-1 expression by silencing Notch2 or by treatment with AMG-176 was able to restore the response of CLL cells to venetoclax. The expression of Notch2 identifies a subset of CLL patients, mainly harboring trisomy 12, characterized by high levels of Mcl-1. This biological mechanism may compromise an effective response to venetoclax.